2022
DOI: 10.3847/1538-4357/ac6102
|View full text |Cite
|
Sign up to set email alerts
|

Postexplosion Positive Jet-feedback Activity in Inner Ejecta of Core Collapse Supernovae

Abstract: We conduct three-dimensional hydrodynamical simulations of weak jets that we launch into a core collapse supernova (CCSN) ejecta half an hour after the explosion and find that the interaction of the fast jets with the CCSN ejecta creates high-pressure zones that induce a backflow that results in mass accretion onto the newly born neutron star. In cases of weak jets, with a total power of ≈1045–1046 erg, the backflow mass accretion might power them up to more energetic jets by an order of magnitude. In total, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…I concluded that late (post-explosion) jets are the most likely explanation for the bump. Late sources of accreted mass that might lead to late jet-launching include fallback after the explosion (e.g., Della Valle et al 2006;Moriya et al 2010;Akashi & Soker 2022;Pellegrino et al 2022), feeding the young NS (or BH) by an inflated main sequence companion (e.g., Ogata, Hirai, & Hijikawa 2021;Hober, Bear, & Soker 2022), and the feeding of a pre-existing NS/BH by the CCSN ejecta (e.g., Fryer, Rueda, & Ruffini 2014;Becerra et al 2015Becerra et al , 2019Akashi & Soker 2020). At this time I leave all possibilities open for SN 2019zrk, as it is not clear whether it was a CCSN event or a CEJSN event.…”
Section: Powering the Bump With Jetsmentioning
confidence: 99%
“…I concluded that late (post-explosion) jets are the most likely explanation for the bump. Late sources of accreted mass that might lead to late jet-launching include fallback after the explosion (e.g., Della Valle et al 2006;Moriya et al 2010;Akashi & Soker 2022;Pellegrino et al 2022), feeding the young NS (or BH) by an inflated main sequence companion (e.g., Ogata, Hirai, & Hijikawa 2021;Hober, Bear, & Soker 2022), and the feeding of a pre-existing NS/BH by the CCSN ejecta (e.g., Fryer, Rueda, & Ruffini 2014;Becerra et al 2015Becerra et al , 2019Akashi & Soker 2020). At this time I leave all possibilities open for SN 2019zrk, as it is not clear whether it was a CCSN event or a CEJSN event.…”
Section: Powering the Bump With Jetsmentioning
confidence: 99%